ANALISIS PENGARUH PERUBAHAN IKLIM DAN KUALITAS GETAH KARET TERHADAP PENDAPATAN PETANI KARET - Hadi, Nafik Umurul; Hardiansah, Hardiansah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Climate change which includes increasing air and sea surface temperatures and changing precipitation patterns can harm the rubber plantation agricultural sector, by maintaining good rubber latex quality and optimizing rubber production, farmers can increase their income in the face of climate change that can affect agriculture, including rubber plantations. The purpose of this study was to determine the effect of climate change and the quality of rubber latex on the income of rubber farmers. The method used in this research is descriptive quantitative with analysis using Partial Least Square (PLS). This study uses primary data sources from questionnaires regarding climate change and the quality of rubber latex on the income of rubber farmers. This study set a target population of 500 rubber farmers with a sample of 83 rubber farmers. The results of the study prove that partial (1) Climate Change (X1) has a positive and significant effect on the income of Rubber Farmers' Income (Y) the P Values are 0.000 <0.05 so that H1 is accepted; (2) Rubber latex quality (X2) has a positive and significant effect on rubber farmers' income (Y). P values of 0.000 <0.05 H2 are accepted; (3) Climate Change and Rubber Sap Quality at (Y) Rubber Farmer Income 73.9%